Optimization Design and Internal Flow Field Study of Open-Design Vortex Pump - Xiongfa Gao; Weidong Shi; Ruijie Zhao; Ting Zhao; Hongfei Wang (Shock and Vibration)
To determine the influences of the main structural parameters on open-design vortex pump performance, optimize the vortex pump performance, and reduce the running vibration and improve stability, orthogonal testing method was introduced in this paper. The selected main factors included impeller outer diameter (D2), impeller outlet width (b2), outlet setting angle of impeller (β2), and inlet setting angle of impeller (β1), and the nine types of impellers were coded according to orthogonal table. After obtaining the preliminarily optimum value range for each factor through range analysis, comprehensive analysis was employed based on the orthogonal test to investigate the main factors and identify the primary and secondary influencing factors affecting the performance of the vortex pump. An optimization scheme was obtained for further design. The results show that the numerical calculation results of the optimization scheme pump are in good agreement with the test results, and it shows the feasibility of the numerical calculation method. The testing results showed that efficiency and head of the optimal model were 4.2% and 9 m higher than those of the prototype model, respectively. Improved efficiency and head met the design requirements. The orthogonal testing method proved the feasibility of performance optimization of the vortex pump. The backflow occurs at the pump entrance and rotates in the same direction with impeller. It moves along the pipe wall from the lateral cavity to the inlet and encourters with the approaching flow.